Analysis of Caffeine Content and other Mineral Components in Different Coffee Germplasms Grown in Pokhara, Nepal - Adhikari Dhungana, Sabitri; Aryal, Lok N. (NPRC Journal of Multidisciplinary Research, 2025)
Caffeine present in coffee is the main reason to make it a world-famous drink. It poses health benefits if consumed in limit. Other than caffeine it contains mineral components that poses health benefits if consumed in limit. Nineteen coffee germplasms; exotic and local collections were studied for their caffeine and mineral components in respective two years. Caffeine content of the tested germplasms was ranged from 0.27 to 0.75 in 2016 and 0.32 to 1.02 in 2017. Study of other mineral components like crude protein (CP%), crude ash (CA%), crude fibre (CF%), phosphorus (P), calcium (Ca) and Iron (Fe) showed and an interesting relationship with caffeine content in specific germplasms. The percentile difference in mineral components was positive among the high and low caffeine-producing germplasms in general. High caffeine-containing germplasm was reported with less chemical components and vice versa in the overall analysis. This study supports the value of antioxidant property of coffee drink to protect the body against diseases. Further studies are needed to clarify the effect of the environmental condition and such properties of coffee.